Dramatically changing rates and reasons for hospitalization in multiple sclerosis - Marrie, Ruth Ann (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: We aimed to describe hospitalizations in the multiple sclerosis (MS) population, and to evaluate temporal trends in hospitalizations in the MS population compared to the general population. METHODS: Using population-based administrative data, we identified 5,797 persons with MS and a matched general population cohort of 28,769 persons. Using general linear models, we evaluated temporal trends in hospitalization rates and length of stay in the 2 populations over the period 1984–2011. RESULTS: In 1984 the hospitalization rate was 35 per 100 person-years in the MS population and 10.5 in the matched population (relative risk [RR] 3.33; 95% confidence interval: 1.67–6.64). Over the study period hospitalizations declined 75% in the MS population but only 41% in the matched population. The proportion of hospitalizations due to MS declined substantially from 43.4% in 1984 to 7.8% in 2011. The 3 most common non–MS-related reasons for admission in the MS population were diseases of the digestive, genitourinary, and circulatory systems. Admissions for bacterial pneumonia, influenza, urinary tract infections, and pressure ulcers occurred more often in the MS population than in the general population, while admissions for circulatory system disease and neoplasms occurred less often. Older age, male sex, and lower socioeconomic status were associated with increased hospitalization rates for non–MS-related reasons. CONCLUSIONS: Although hospitalization rates have declined dramatically in the MS population over the last quarter century, they remain higher than in the general population. Admissions for MS-related reasons now constitute only a small proportion of the reasons for hospitalization.